Risk Factors for Neonatal Death in Konawe Islands District - Badriah, Siti; Amraeni, Yunita; Tasnim, Tasnim (Magister Kesehatan Universitas Mandala Waluya, 2023)
Background: The prevalence of neonatal mortality rate of Konawe Islands Regency in 2019 was 22 per 1000 live births, in 2020 it was 26.2 per 1000 live births and experienced a significant increase in 2021 to 34.9 per 1000 live births (Konawe Islands Regency Health Office 2019-2021). The purpose of the study was to analyze the risk factors of Mothers, Infants, Work and Postpartum care for Neonatal deaths in the Konawe Islands Regency. Methods: This study used a Case Control Study approach. The population numbered 48 people. The Study Sample totaled 24 case samples and 24 control samples. The sample technique in this study is Simple Random Sampling. The data is processed using the Odds Ratio Test. Result: The results showed that the gestational age or 7,286 LL value 2,034 and UL 26,102, PARITY OR 3,215 LL value 0.902 and UL value 11,460, disease history OR 6,000 LL value 1,711 and UL value 21,038, BMI OR 4,200 LL value 1,228 and UL value 14,365, against Neonatal deaths in the Konawe Islands Regency Area. Conclusion: The conclusions in this study show that maternal factors, infant factors and postpartum care are risk factors while occupation is not a risk factor for neonatal mortality in the Konawe Islands Regency. It is expected for the Health Office and Puskesmas to always provide education in the form of counseling and counseling related to maternal and child health to reduce neonatal death cases.